In the context of a daycare center: nursing and their representations ofchild care as an educational act - Sarubbi, Vicente [UNESP]; Muylaert, Camila Junqueira [UNESP]; Gallo, Sophia Motta [UNESP]; Gallo, Paulo Rogério [UNESP] (Universidade de São Paulo, Escola de Enfermagem, 2014)
This study aimed to analyze the social representations in the professionals of technicalstaff, who work with children at USP daycare centers. Eight professionals of the nursingfield underwent a semi-structured interview. The interviews were recorded and transcribedin their entirety and the content of the discourse was subjected to thematic-categoricalanalysis. The categories were transformed into variables and processed by the softwareClassification Hiérarchique Classificatoire et Cohésitive (CHIC®) and analyzed by thehierarchical similarity tree. The results indicate that actions to promote health arereported as educational and transformative, in which health care gains new meaning throughcontextualized conceptions in the field of child education. We conclude that professionalsattribute new meanings to their practices in the health care environment of daycarecenters as their representations shifts from the logic of the biomedical field to a logicof educational care. In this sense, they perceive themselves as being challenged toestablish an interaction with the children in terms of their activities related to thepromotion of health and in an educational act.

El objetivo de la investigación estudio fue analizar las representaciones sociales de lostécnicos profesionales que trabajan en los centro de atención infantil de la Universidadde São Paulo (USP). Ocho profesionales de enfermería fueron entrevistados mediante unsemi-estructurada guión. Las entrevistas fueron grabadas y transcritas y sometidas alanálisis de contenido temático-categorial. Las categorías se transformaron en variablesprocesadas por hiérarchique Classificatoire et Cohesiva software Clasificación (CHIC®) yanalizados por similitud árbol jerárquico (clúster de múltiples niveles). Los resultadosindican que las acciones sobre promoción de la salud se reportan como educativo ytransformador, en que la atención de la salud adquiere nuevos significados a través deconcepciones contextualizadas en el campo de la educación infantil. Llegamos a laconclusión de que los profesionales atribuyen nuevos significados a sus prácticas en elámbito sanitario de los centro de atención infantil sus representaciones turnos desde lalógica del campo de la biomedicina a la lógica de la atención educativa. En este sentido,los propios que perciben al ser desafiados a establecerse una interacción con los niños entérminos de sus actividades relacionadas con la promoción de la salud y en un actoeducativo.
En el contexto de la guardería: enfermería y sus representaciones de cuidadoinfantil como un acto educativo
Keywords: nursing; Day care centers; Child care; health education